Legal Review On The Consensuality Principle Of Buy And Sale Contract In Property Rights Object (Comparison Between The Civil Code And Islamic Law) - Sutriyono, Sutriyono (CV. Inara, 2022)
The purpose of this study is first, to examine and analyze the sale and purchase contract in the Civil Code. Second, to examine and analyze the similarities and differences between the Civil Code and Islamic law on the principle of consensuality in buying and selling contracts. This research method uses a normative juridical approach. This study emphasizes the steps of normative and qualitative juridical analysis. Based on the theme of this study, and the formulation of the problem, the researchers used a normative juridical approach. The specification of this research is descriptive analytical research. The results of the study show that 1) In the Civil Code, consensuality is the main cause of buying and selling. At the moment of agreement, the sale and purchase has occurred. Likewise in Islamic law, the agreement is an element of buying and selling, but it is not enough just to agree, but the terms and conditions of sale and purchase must be fulfilled. Therefore, Islamic law adheres to the principle of consensuality accompanied by other requirements. 2) The implications of applying Article 1458 of the Civil Code are positive and negative. The positive is that people will easily make a sale and purchase agreement. But along with that there is a negative that is very easy for fraud or fraud from one party.